Pemanfaatan Perjanjian Kerja Sebagai Perlindungan Terhadap Pekerja Outsourcing - Hanun, Lalita Maida Listiyani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The application of the outsourcing system in assisting business activities has become a strategy that is considered efficient in the business world. The use of outsourced workers as helpers in doing the company's supporting work has efficiency so that the company can focus on its core work or production to the fullest. Even so, there are often violations and neglect committed by the company against workers, making workers experience exploitation and discrimination from the company. Outsourced workers are exploited by being worked on continuously as outsourced workers without regard to existing regulations and without regard to justice for workers. Discrimination is found in the clear differences in rights between permanent and outsourced workers, some of which violate the rules. The misrepresentation of the rules that occurs here makes workers realize the importance of a Work Agreement for the certainty of the rights and guarantees they will receive. The Work Agreement is one way for workers to avoid exploitation and discrimination in the world of work.